University Pathways of Graduate Students: Professionalization, Innovation and Identity. A French-Argentine Comparative Study (European Journal of Social Science Education and Research, 2022)
This article presents findings from two studies carried out with fourth level university students in Argentina, namely Argentine PhDs working at UNCuyo, and with a second group made up of PhDs who are taking part in Professionalization programs (Programs of International Cooperation) in France. This is a comparative study. It is thought that after showing a certain level of excellence and being in contact with other cultures, differences between the groups may exist in terms of perspectives for future work, the role of innovation and competencies to be developed. Various hypotheses were considered. Both studies included common variables related to issues that affect, on the one hand, the effectivity and quality of the University as it relates to the working world and, on the other hand, personal and professional pathways. We focused on Professionalization, Identity and Innovation, variables that involve individuals and contexts interacting with one another. The methodology was quanti-qualitative. Techniques used were semi-structured surveys, interviews and focus groups. The findings show convergences, divergences and silences in the different groups with respect to Innovation, both in its conception and roots and with respect to the future world of work (effects). The findings renew interest in education and employment policies in the face of the demands and changes that the future workplace will require.